Effects of Age, Sex, Personality Traits, and Social Support on Successful Aging: A Longitudinal Study of Older Adults in Sukabumi City - Weldemina Yudit Tiwery; Istiana Heriani; Devi Rusvitawati (Westscience Press, 2023)
This longitudinal study investigated the effect of age, sex, nursing care characteristics, and social support on successful aging outcomes among elderly adults in KotaSukabumi, Indonesia. 260 participants completed baseline assessments and a 12-month follow-up on physical health, psychological well-being, and social engagement. Results showed that social support was positively associated with all three successful aging outcomes at follow-up, while nursing care characteristics were positively related to social engagement at follow-up. Age was negatively associated with physical health and social engagement at follow-up, and gender was not significantly related to successful aging outcomes. These findings emphasize the importance of social support and nursing care in promoting successful aging and suggest that interventions to improve these factors could effectively improve the health and well-being of elderly adults.